Refreshing the design of a regional economic growth model in the context of the new digital decade - Zlati, Monica Laura; Fortea, Costinela; Antohi, Valentin-Marian; Cristache, Nicoleta; Dinca, Marius Sorin; Balsalobre-Lorente, Daniel (Technological and Economic Development of Economy, 2025)
The digital economy is a significant objective of future development of the European space and is included alongside other strategic objectives in the 2030 and 2050 Agenda of the European Union. According to the European Union’s Digital Economy and Society Index (DESI), the Nordic countries (Finland, Denmark, the Netherlands, and Sweden) are the top performers of the European Union. In the same time, Romania ranks last in the 2022 ranking. Current research analyses the four areas of the digital economy (human capital, digital technology integration, connectivity, and digital public services) in a mix that is correlated with regional indicators of sustainable development to design a regional model of digital economy growth. The methods of study include restructuring the DESI rankings and regional reclassification based on the criteria of correlative ranking of digital economy indicators in correlation with sustainable development indicators and the design of structural equations. The study results will form the basis of a public policy proposal to accelerate digital development for disadvantaged European regions.First published online 24 September 2025